2014
DOI: 10.1557/opl.2014.574
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Vibrations in Index-Identified Carbon Nanotubes

Abstract: Combining high resolution transmission electron spectroscopy, electron diffraction, and resonant Raman spectroscopy experiments on the same suspended (free-standing) individual carbon nanotubes is the ultimate approach to relate unambiguously the structure and the intrinsic phonon features of these nano-systems.By using this approach, the effect of coupling between nanotubes on the phonons is investigated in two model nano-systems: (i) a bundle of two non-identical SWNTs (inhomogeneous dimer), (ii) double-wall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 11 publications
0
16
0
3
Order By: Relevance
“…It was previously found that in the framework of the atomistic model, RBLM frequencies of (12,8)@(16,14) DWNT are best described, if C e ¼ 0.065 for the outer layer and C e ¼ 0 for the inner layer are considered. 6,11 Because all DWNTs, studied in this work, were synthesized following the similar procedure, we use the same C e values. Under this assumption, we find that the calculated G norm values for our DWNTs (red rhombs in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously found that in the framework of the atomistic model, RBLM frequencies of (12,8)@(16,14) DWNT are best described, if C e ¼ 0.065 for the outer layer and C e ¼ 0 for the inner layer are considered. 6,11 Because all DWNTs, studied in this work, were synthesized following the similar procedure, we use the same C e values. Under this assumption, we find that the calculated G norm values for our DWNTs (red rhombs in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5] Recently, more evolved experiments using combinations of different complementary techniques (e.g., atomic force microscopy, electron diffraction (ED), and resonant Raman spectroscopy) were performed by our and other groups to measure Raman spectra of individual DWNTs and to study the effects of van der Waals interaction. [6][7][8][9][10][11] In our recent work, combining high-resolution transmission electron microscopy (HRTEM), ED, and resonant Raman spectroscopy on individual free-standing DWNTs, 11 we have shown that the strength of this "inner" tube-"outer" tube interaction, which is dependent on the interlayer distance in DWNTs, strongly affects the out-of-phase radial breathing-like mode (RBLM) frequencies. We thus proposed that the positions of the radial breathing-like modes (RBLMs) and the difference between experimental and theoretical calculations within atomistic valence force field model 12 can be used as criteria to evaluate diameters of the inner and outer tubes in nonindex-identified DWNTs.…”
Section: Introductionmentioning
confidence: 99%
“…1, a). Двустенные индивидуальные горизонтально-ориентированные углеродные нанотрубки были получе-ны для исследований методом каталитического химиче-ского осаждения из парогазовой фазы (CCVD), который был ранее описан в работах [14][15][16][17][18][19][20][21]. Рост ДУНТ проис-ходил либо на специально подготовленных кремниевых подложках со сквозными траншеями (см.…”
Section: особенности методики исследованийunclassified
“…рогазовой фазы (CCVD), который ранее описывался в работах [3,4,[13][14][15][16][17][18]. Использованные нами эксперимен-тальные протоколы синтеза позволяют получать сверх-длинные нанотрубки (до 5 cm), способные в процессе роста преодолевать траншеи (шириной в миллиметры) и барьеры (высотой 500 µm).…”
Section: синтез и методика исследованийunclassified
“…Типичная процедура определения индексов хиральности (n, m) на-нотрубки заключается в вычислении диаметра d ОУНТ по частоте радиально-дыхательной моды (RBM) с после-дующим сопоставлением теоретических и эксперимен-тальных энергий электронных переходов E ii по графику Катаура [2][3][4][5][6][7]. Следует отметить, что успешность приме-нения этой методики напрямую зависит от окружения, в котором находится нанотрубка [8].…”
Section: Introductionunclassified